Efficacy and safety of magnetic resonance-guided focused ultrasound for Parkinson’s disease: a systematic review and meta-analysis - Tian, Xiaona; Hu, Rongrui; He, Peicong; Ye, Jianhong (Frontiers in Neurology, 2023)
Objective Magnetic resonance imaging-guided focused ultrasound (MRgFUS) is a novel noninvasive treatment for drug-resistant Parkinson’s disease (PD) related tremor. This study aims to evaluate MRgFUS’s efficacy and safety in PD through a systematic review and meta-analysis, examining pre-and post-treatment MDS-UPDRSIII and/or CRST scores and associated adverse events. Materials and methods We conducted an extensive literature search across PubMed, Embase, Web of Science, and Cochrane Library databases, screening studies based on set criteria and analyzing MDS-UPDRSIII, CRST, and adverse events pre- and post-MRgFUS treatment. Results Out of 468 retrieved articles, 20 studies involving 258 patients, spanning 2014–2023, were included.17 studies indicated significant MDS-UPDRSIII score reductions post-MRgFUS treatment, while 3 showed significant CRST score declines. In the “on” medication state, pooled MDS-UPDRSIII scores at 1, 3, 6, and 12 months were 12.18 (95% CI: 5.83–18.52), 12.10 (95% CI: 8.22–15.97), 14.85 (95% CI: 9.28–20.41), and 20.65 (95% CI: 12.15–29.14) respectively. In the “off” state, scores were 11.45 (95% CI: −3.50-26.40), 14.71 (95% CI: 4.95–24.46), 21.52 (95% CI: 19.28–23.75), and 22.28 (95% CI: 15.26–29.30). Adverse events were typically mild and transient, with speech disturbances, ataxia, and sensory abnormalities being common post-operative neurological complications. Conclusion MRgFUS offers an effective and relatively safe treatment option for patients with drug-resistant PD-related tremor. Systematic review registration https://www.crd.york.ac.uk/prospero/, No. CRD42023428332.